Moriello's small animal dermatology, fundamental cases and concepts : self-assessment color review - Berger, Darren J.; Moriello, Karen A. (Boca Raton : CRC Press, 2019)
Karen Moriello's seminal book has been completely updated in an effort to create a true two-volume set highlighting fundamental and advanced concepts. This revised fundamental edition includes all new cases and nearly 300 new images. The guide uses a case-based format to deliver a general overview of dermatology of the dog and cat, providing a reference that mirrors the way veterinarians will encounter different scenarios at random in real-life practice. It uses self-assessment problems to review the most common skin diseases encountered every day, plus some more obscure diseases that a veterinarian will face.
OCLC-licensed vendor bibliographic record.
Keywords: Veterinary dermatology; Pet medicine; MEDICAL / Veterinary Medicine / General; MEDICAL / Veterinary Medicine / Food Animal; MEDICAL / Veterinary Medicine / Small Animal